A skin-interfaced three-dimensional closed-loop sensing and therapeutic electronic wound bandage - Huang, Xingcan; Zhang, Qiang; Yang, Yawen; Chow, Lung; Ma, Jie; Xu, Guoqiang; Guo, Fang; He, Xinxin; Li, Zhiyuan; Zhao, Guangyao; Su, Jingyou; Guo, Guihuan; et al. (Nature communications, 2025)
Chronic wound healing is a complex and long-standing problem, that has been a major and critical clinical concern around the world for years. Recent advances in digital wound dressings open new possibilities for solving the problem. Here, we report a battery-free, fully permeable, skin-adhesive, stretchable electronic wound bandage (iSAFE) for intelligent wound management. This electronic bandage exhibits superior properties in multiple features and can be conformally adhered to the skin wound. In addition, the iSAFE can accurately assess the wound conditions in-situ and thus adaptively perform localized drug release. The results from both in vitro and in vivo studies on animals prove the validity of wound monitoring, wound healing boosting and intelligent closed-loop wound management. Clinical trials on patients across age 18 to 95 with various types of wounds are performed. These results all indicate the unique and universality of the reported technology for wound monitoring and management. Electronic wound bandages have to balance conformability and wound healing properties. Here, the authors develop a smart patch (iSAFE) using biomaterials with bioelectronics to facilitate permeability with waterproofing. This achieves intelligent wound management with real-time wound monitoring and active therapy.